Contrasted fate of zinc sulfide nanoparticles in soil revealed by a combination of X-ray absorption spectroscopy, diffusive gradient in thin films and isotope tracing. (1st January 2022) - Le Bars, Maureen; Legros, Samuel; Levard, Clément; Chevassus-Rosset, Claire; Montes, Mélanie; Tella, Marie; Borschneck, Daniel; Guihou, Abel; Angeletti, Bernard; Doelsch, Emmanuel
Abstract: Incidental zinc sulfide nanoparticles (nano-ZnS) are spread on soils through organic waste (OW) recycling. Here we performed soil incubations with synthetic nano-ZnS (3 nm crystallite size), representative of the form found in OW. We used an original set of techniques to reveal the fate of nano-ZnS in two soils with different properties. 68 Zn tracing and nano-DGT were combined during soil incubation to discriminate the available natural Zn from the soil, and the available Zn from the dissolved nano- 68 ZnS. This combination was crucial to highlight the dissolution of nano- 68 ZnS as of the third day of incubation. Based on the extended X-ray absorption fine structure, we revealed faster dissolution of nano-ZnS in clayey soil (82% within 1 month) than in sandy soil (2% within 1 month). However, the nano-DGT results showed limited availability of Zn released by nano-ZnS dissolution after 1 month in the clayey soil compared with the sandy soil. These results highlighted: (i) the key role of soil properties for nano-ZnS fate, and (ii) fast dissolution of nano-ZnS in clayey soil. Finally, the higher availability of Zn in the sandy soil despite the lower nano-ZnS dissolution rate is counterintuitive. This study demonstrated that, in addition to nanoparticle dissolution, it is also essential to take the availability of released ions into account when studying the fate of nanoparticles in soil. Graphical abstract: Image 1 Highlights: Incubation experiments were designed to assess the fate of nano-ZnS in 2 contrasted soils. 68 Zn-labelled nano-ZnS were used to trace Zn released by nanoparticles dissolution. Nano-ZnS dissolution and Zn availability is strongly soil-dependent. XAS determined Zn speciation revealed a fast nano-ZnS dissolution in the clayey soil. Higher availability of Zn was detected in the sandy soil despite lower dissolution rate.